Children’s Academic, Artistic, and Athletic Competencies: Successes Are in the Eye of the Beholder - Racz, Sarah J.; Putnick, Diane L.; Esposito, Gianluca; Bornstein, Marc H. (Frontiers in Psychology, 2019)
A significant challenge to fully understanding children’s academic and other competencies is dependency of the determination on the method of study, including notably who makes the assessment. This study examined similarities and differences in child, mother, father, and teacher reports of children’s competencies across multiple domains of math, reading, music, and sports from two separate perspectives of rater agreement, mean level and order association. Two hundred and sixty-seven European American families were recruited from the mid-Atlantic region of the United States, and children, mothers and fathers, and teachers completed a commonly used rating measure of children’s competencies when the children were 10 years of age. Results showed (1) high levels of order agreement (perhaps reflecting the observable nature of children’s competencies), (2) some systematic mean level differences across raters, and (3) little inter-domain agreement (except among teachers, which may reflect teachers’ unique perspectives on children’s competencies). The educational, developmental, and methodological implications of the findings are discussed in the context of children’s school performance. Who makes the determination of children’s several different competencies matters.